Correlation of renal volume to renal function and blood pressures in low birth weight children - Ekawaty Larope; Adrian Umboh; Rocky Wilar (Indonesian Pediatric Society, 2014)
Background Disruption of nephrogenesis in low birth weight(LBW) infant leads to decreases in nephron number andrenal volume, resulting in renal hyperfunction and eventually,hypertension.Objective To assess for a possible correlation of renal volume torenal function and blood pressures in low birth weight childrenaged 7 -8 years.Methods We conducted a retrospective cohort study on childrenaged 7-8 years in Manado, who were born LBW or n ormalbirth weight (NBW). Renal function was assessed by measuringblood cyctatin-C level while renal volume was determined usingultrasound measurements of renal length x width x thickness(cm3). Ttest was used to compare renal volume and cystatin-Clevels in LBW children to NBW children. Pearson's correlationtest was used to assess the relationship of renal volume to renalfunction and blood pressure in low birth weight children.Results Subjects were 48 LBW and 48 NBW children. Meanrenal volumes were 7 8.28 (SD 7 .96) cm3 in the LBW group and103.68 (SD 12.52) cm3 in the NBW group (P< 0.01). The meancystatin-C levels, as a measure of renal function, were 0.81 (SD0.07) mg/Lin the LBW group and in 0.73 (SD 0.06) mg/Linthe NBW group (P< 0.01). There was no correlation betweenrenal volume and cystatin-C level (r=-0.169; P>0,05) as wellas between renal volume and systolic (r=-0.07, P>0.05) anddias tolic blood pressure (r=-0.123, P>0.05).Conclusion Mean renal volume is lower in the LBW groupthan in the NBW group, but is not correlated to decreased renalfunction or blood pressures.